2010
DOI: 10.1017/s1460396909990173
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication and information provision in radiotherapy—the role of radiation therapists

Abstract: Introduction: Health professionals have a duty of care to radiotherapy patients in providing them with adequate information before treatment. There is a lack of research that describes the roles of radiation therapists and radiation oncology nurses in providing information to patients. This study aimed to:(1) explore how radiation therapists communicate with breast cancer patients during a radiotherapy planning appointment;(2) determine what information is provided during this appointment and (3) explore radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 30 publications
2
55
0
Order By: Relevance
“…This finding suggests that there is a need to identify these patients in clinical practice and reduce their perceived room for improvement in well-being by alleviating their anxiety and improving their perceptions of care 50. There have been some partially successful intervention studies conducted in radiotherapy settings 51 52 and more generally3 that have aimed to improve patient-centredness of care.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that there is a need to identify these patients in clinical practice and reduce their perceived room for improvement in well-being by alleviating their anxiety and improving their perceptions of care 50. There have been some partially successful intervention studies conducted in radiotherapy settings 51 52 and more generally3 that have aimed to improve patient-centredness of care.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Halkett et al, RTs indicated that they feel uncomfortable screening for and managing the symptoms of anxiety and depression [10]. In order to fulfil the requirements of the CCO practice guidelines, it is imperative that RTs are routinely screening for symptoms of emotional distress: anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…During our observations of usual care we found that information provided does not comply with the literature on preparing patients for threatening procedures, very little sensory or procedural information is given (if at all) and radiation therapists do not spend time eliciting or addressing patients’ fears and concerns 32. Furthermore, radiation therapists often do not have the opportunity to follow patients up when they start treatment or provide continuity of care.…”
Section: Introductionmentioning
confidence: 93%